ShadowBlock: A Lightweight and Stealthy Adblocking Browser - Zhu, Shitong; Iqbal, Umar; Wang, Zhongjie; Qian, Zhiyun; Shafiq, Zubair; Chen, Weiteng (The World Wide Web Conference, 2019)
As the popularity of adblocking has soared over the last few years, publishers are increasingly deploying anti-adblocking paywalls that ask users to either disable their adblockers or pay to access content. In this work we propose ShadowBlock, a new Chromium-based adblocking browser that can hide traces of adblocking activities from anti-adblockers as it removes ads from web pages. To bypass anti-adblocking paywalls, ShadowBlock takes advantage of existing filter lists used by adblockers and hides all ad elements stealthily in such a way that anti-adblocking scripts cannot detect any tampering of the ads (e.g., absence of ad elements). Specifically, ShadowBlock introduces lightweight hooks in Chromium to ensure that DOM states queried by anti-adblocking scripts are exactly as if adblocking is not employed. We implement a fully working prototype by modifying Chromium which shows great promise in terms of adblocking effectiveness and anti-adblocking circumvention but also more efficient than the state-of-the-art adblocking browser extensions. Our evaluation on Alexa top-1K websites shows that ShadowBlock successfully blocks 98.3% of all visible ads while only causing minor breakage on less than 0.6% of the websites. Most importantly, ShadowBlock is able to bypass anti-adblocking paywalls on more than 200 websites that deploy visible anti-adblocking paywalls with a 100% success rate. Our performance evaluation further shows that ShadowBlock loads pages as fast as the state-of-the-art adblocking browser extension on average.